Chiari - like malformation and syringomyelia in a toy poodle - a potential link to central nervous system inflammation - Andric, ND; Nešić, SN; Gielen, I; Andrić, JF (Journal of the Hellenic Veterinary Medical Society, 2025)
A one-year-old female Toy poodle was referred for seizures, phantom scratching behind the right ear, and inability to jump. An intracranial and cervical spinal cord disorder was suspected. The cerebrospinal fluid analysis showed pleocytosis, increased total proteins, serum amyloid A (SAA), and lactate concentration, low albumin ratio, increased lactate dehydrogenase (LDH) activity, and no active forms of matrix metalloproteinase (MMPs). Magnetic resonance imaging of the brain and cervical part of the spinal cord revealed caudal cerebellar tonsil herniation and a syrinx formation between the C2 and C7 parts of the spinal cord. Chiari-like malformation (CM) and Syringomyelia (SM) as the result of a CM was diagnosed. Histopathology verified the presence of syrinxes in the dorsal region of the spinal cord, with and without connection to the central canal. For the first time, SAA, MMPs, lactate, and LDH were measured in CSF of dogs with CMSM, suggesting a potential link to central nervous system inflammation.